2003
DOI: 10.1385/bter:91:3:231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Vitamin E and Selenium on Antioxidative Defense Mechanisms in the Liver of Rats Treated with High Doses of Glucocorticoid

Abstract: The aim of this work was to determine the effects of dietary intake vitamin E and selenium (Se) on lipid peroxidation as thiobarbituric acid reactive substances (TBARS) and on the antioxidative defense mechanisms in the liver of rats treated with high doses of prednisolone. Two hundred fifty adult male Wistar rats were randomly divided into five groups. The rats were fed a normal diet, but groups 3, 4, and 5 received a daily supplement in their drinking water of 20 mg vitamin E, 0.3 mg Se, and a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…LPO, was enhanced by high doses of prednisolone in the kidneys of rats, as was the case in our earlier observations in the liver, 9 and that vitamin E and Se minimized these effects. It was found that high doses of GCs led to oxidative stress in the whole body, since the TBARS concentration in plasma increased.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…LPO, was enhanced by high doses of prednisolone in the kidneys of rats, as was the case in our earlier observations in the liver, 9 and that vitamin E and Se minimized these effects. It was found that high doses of GCs led to oxidative stress in the whole body, since the TBARS concentration in plasma increased.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are almost identical to our earlier observations in the liver. 9 It is likely that in the kidney, vitamin E prevents the formation of LPO caused by high dose GC by scavenging free radicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractions of testes (500 mg) were homogenized in buffer [Tris 10 mM, ethylenediaminetetraacetic acid (EDTA) 1 mM, PMSF 1 mM, pH=7.5; Sigma-Aldrich Chemicals, St. Louis, MO, USA)]. The homogenates were centrifugated at 600 × g for 10 min and recentrifugated at 13,000 × g for 20 min at 4 C to obtain a postnuclear homogenate and postmitochondrial supernatant fractions [19].…”
Section: Tissue Preparationmentioning
confidence: 99%
“…Of particular interest is the increased SOD level observed in ducklings from the maternal high-vitamin premix group. The effects of dietary vitamins on antioxidant enzyme activities remain controversial (Musalmah et al, 2002;Beytut and Aksakal, 2003).…”
Section: Discussionmentioning
confidence: 99%